Subclinical atherosclerosis at peripheral arteries in obese individuals: Subclinical atherosclerosis in obese - Farinetti, Alberto; Casteniere, Ivana; Clini, Enrico; Migaldi, Mario; Gelmini, Roberta; Scaringi Raspagliesi, Flavia; Ara, Nicoletta; Serra, Francesco; Spatafora, Francesco; Genazzani, Alessandro; Mattioli, Anna Vittoria (Progress in Nutrition, 2021)
Evidence on relationship between obesity and peripheral arterial disease (PAD) are controversial. The aim of the present study is to evaluate the presence of subclinical atherosclerosis at all level of the explorable vascular segments with a systematic method in a selected population of young obese submitted to a comprehensive rehabilitation course. A group of 50 consecutive morbidly obese (BMI>30) was included. All patients underwent Doppler evaluation including intima media thickness (IMT) and presence/absence of plaques. Results.We found that vessels in the upper segment of the body demonstrate the presence of thickening and/or plaques at the level of the carotid segments but not of the subclavian arteries. The IMT of the right Common Carotid Artery (CCA) (1.49 + 1.38 versus 0.62 + 0.23; p=0.037) and of the left CCA (1.66 + 1.89 versus 0.45 + 0.26; p=0.034) was greater in patients. Vessels of the lower segment demonstrate the presence of thickening and/or plaques at the iliac but not at femoral level. The control group did not present vessel thickening at any level. In conclusions asymptomatic vascular damage may be present in different segment of peripheral vessels, thus suggesting an early risk for developing an overt vascular disease over time in obese.